Ultrafast carrier dynamics at organic donor–acceptor interfaces—a quantum-based assessment of the hopping model. (10th January 2022) - Dorfner, Maximilian F X; Hutsch, Sebastian; Borrelli, Raffaele; Gelin, Maxim F; Ortmann, Frank
Abstract: We investigate the charge transfer dynamics of photogenerated excitons at the donor–acceptor interface of an organic solar cell blend under the influence of molecular vibrations. This is examined using an effective Hamiltonian, parametrized by density functional theory calculations, to describe the full quantum behaviour of the relevant molecular orbitals, which are electronically coupled with each other and coupled to over 100 vibrations (via Holstein coupling). This electron–phonon system is treated in a numerically quasi-exact fashion using the matrix-product-state (MPS) ansatz. We provide insight into different mechanisms of charge separation and their relation to the electronic driving energy for the separation process. We find ultrafast electron transfer, which for small driving energy is dominated by kinetic processes and at larger driving energies by dissipative phonon emission connected to the prevalent vibration modes. Using this fully quantum mechanical model we perform a benchmark comparison to a recently developed semi-classical hopping approach, which treats the hopping and vibration time scales consistently. We find qualitatively and quantitatively good agreement between the results of the sophisticated MPS based quantum dynamics and the simple and fast time-consistent-hopping approach.